2017
DOI: 10.1038/cddis.2017.316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-grade human umbilical cord-derived mesenchymal stem cells reverse cognitive aging via improving synaptic plasticity and endogenous neurogenesis

Abstract: Cognitive aging is a leading public health concern with the increasing aging population, but there is still lack of specific interventions directed against it. Recent studies have shown that cognitive function is intimately affected by systemic milieu in aging brain, and improvement of systemic environment in aging brain may be a promising approach for rejuvenating cognitive aging. Here, we sought to study the intervention effects of clinical-grade human umbilical cord-derived mesenchymal stem cells (hUC-MSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…[ 28 ] Indeed, while the use of animal components carries the risk of zoonoses and xenogeneic immune reactions, [ 29 ] laboratory‐generated hUC‐MSCs do not undergo quality and safety testing that is required for clinical applications. Our group has established a Cell Factory and Biobank at the South China Institute of Biomedicine in Guangzhou that is currently producing clinical‐grade hUC‐MSCs, using methods [ 14 ] that are fully compliant with current Good Manufacturing Practice guidelines, and conform to the quality standards of National Institutes for Food and Drug Control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 28 ] Indeed, while the use of animal components carries the risk of zoonoses and xenogeneic immune reactions, [ 29 ] laboratory‐generated hUC‐MSCs do not undergo quality and safety testing that is required for clinical applications. Our group has established a Cell Factory and Biobank at the South China Institute of Biomedicine in Guangzhou that is currently producing clinical‐grade hUC‐MSCs, using methods [ 14 ] that are fully compliant with current Good Manufacturing Practice guidelines, and conform to the quality standards of National Institutes for Food and Drug Control.…”
Section: Discussionmentioning
confidence: 99%
“…Our past work has characterized beneficial effects of clinical‐grade hUC‐MSC‐based therapies for intervening with normal aging‐related cognitive dysfunction. [ 14 ] However, whether hUC‐MSCs have effects on pathological cognitive decline in AD, needs to be further addressed. Although some studies have showed positive effects of hUC‐MSCs in the treatment of AD, [ 30,31 ] little is known about which core factor secreted from hUC‐MSCs plays important roles in hUC‐MSC‐modulated recovery of cognition function, which may be one of the key factors restricting the better clinical application of hUC‐MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D‐galactose (D‐gal) induced aging model is a systemic and homogeneous aging model, [ 55 ] it was applied to induce NSCs senescence in vitro as described before. [ 56 ] Senescent NSCs were incubated with 1 × 10 10 particles per mL ESC‐sEVs or an equal volume of PBS for 3 passages.…”
Section: Methodsmentioning
confidence: 99%